2017
DOI: 10.18553/jmcp.2017.23.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overactive Bladder Step Therapy Policies on Medication Utilization and Expenditures Among Treated Medicare Members

Abstract: This research was funded by Astellas Pharma Global Development and was conducted as part of the Astellas-Humana Research Collaboration. Ng, Kristy, Schermer, and Bradt are employees of Astellas. Astellas manufactures mirabegron (Myrbetriq) and solifenacin (VESIcare). Abbass, Caplan, Collins, and Suehs are employees of Comprehensive Health Insights, a subsidiary of Humana, which received funding from Astellas for this study. Suehs owns stock in Humana. Chan is an employee of Humana Pharmacy Solutions. Portions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…One facet is insurance programs often necessitating trial of anticholinergics prior to approval of coverage for mirabegron, or step therapy policies. Abbas et al., 12 compared medication utilization before and after discontinuation of a step therapy policy. In this Humana policy, trial of two other anticholinergics was required prior to the approval of fesoterodine and mirabegron.…”
Section: Discussionmentioning
confidence: 99%
“…One facet is insurance programs often necessitating trial of anticholinergics prior to approval of coverage for mirabegron, or step therapy policies. Abbas et al., 12 compared medication utilization before and after discontinuation of a step therapy policy. In this Humana policy, trial of two other anticholinergics was required prior to the approval of fesoterodine and mirabegron.…”
Section: Discussionmentioning
confidence: 99%
“…The initial prescribed antimuscarinic may not be the same as the one dispensed as switching to a less expensive or formulary-preferred medication may have occurred following provider approval. As many other antimuscarinics or mirabegron may not be available to patients due to formulary restrictions and increased co-payment costs, 20 patients may have to choose between oral oxybutynin, which carries the risk of worsening cognition, or no treatment, which may result in sequelae such as falls, depression, or reduced quality of life due to untreated OAB. 4349 Moreover, mirabegron, a beta-3 agonist which improves OAB symptoms without blocking antimuscarinic receptors, may theoretically be a better option than other antimuscarinics; however, medication formularies and costs may make mirabegron difficult to afford for many patients after other antimuscarinics become generic.…”
Section: Discussionmentioning
confidence: 99%
“…11–16,19 However, other antimuscarinics and mirabegron may not be readily available to patients due to formulary restrictions and increased co-payment costs which may lead to the use oral oxybutynin in patients with cognitive impairment or the avoidance of treatment in patients with OAB. 20 Understanding the association between cognitive impairment and costs on the differential prescribing of antimuscarinics may lead to a better understanding of prescribing behavior in the use of oral oxybutynin versus other antimuscarinics. The aim of this study was to evaluate factors suggestive of documented cognitive impairment on the prescribing of oral oxybutynin versus other antimuscarinics in a general population of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that after beta-3 agonists were available in the market, a shift in prescription habits of the physicians has occurred. 13,14 In clinical practice, patients with OAB also present to and are treated by urologists (URO), obstetricians and gynecologists (OB/GYN), and geriatricians (GER). Treatment choices can vary due to several factors and prescription differences may occur between specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that antimuscarinics are the most commonly prescribed drugs, an increase in prescriptions for mirabegron and other central nervous system sparing molecules has occurred. It has also been shown that after beta‐3 agonists were available in the market, a shift in prescription habits of the physicians has occurred 13,14 …”
Section: Introductionmentioning
confidence: 99%